The clinical research of Thinprep Cytology Test (TCT) combined with HPV-DNA detection in screening cervical cancer - Liu, Y.; Zhang, L.; Zhao, G.; Che, L.; Zhang, H.; Fang, J. (Cellular and Molecular Biology, 2017)
Our objective is to explore the clinical value of thinprep cytologic test (TCT) combined with HPV-DNA detection in screening cervical cancer. 420 cervical cancer patients admitted in our hospital between April, 2011-April, 2014 were selected. All patients received TCT and HPV-DNA detection, and cervical tissue biopsy was used to confirm the diagnosis. TCT screening results showed that there were 175 patients were >ASCUS and the positive rate was 41.7%, histopathological screening showed that there were 199 patients were â‰¥cervical intraepithelial neoplasia (CIN) I and the positive rate was 47.4%. HPV-DNA detection showed 180 patients were positive which was 42.9%, and the positive rate of HPV-DNA detection was increased as the disease severity increased. The sensitivity of TCT combined with HPV-DNA detection was higher than single TCT or HPV-DNA, however the specificity was relatively low, and the positive predictive value and negative predictive value were higher which were similar to pathological results. TCT combined with HPV-DNA detection has high sensitivity and accuracy in screening cervical cancer, which is worthy of clinical application.